2001
DOI: 10.1021/bi011653a
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Model for the Allosteric Regulation of Mammalian Ribonucleotide Reductase. Functional Consequences of ATP- and dATP-Induced Oligomerization of the Large Subunit

Abstract: Reduction of NDPs by murine ribonucleotide reductase (mRR) requires catalytic (mR1) and free radical-containing (mR2) subunits and is regulated by nucleoside triphosphate allosteric effectors. Here we present a new, comprehensive, and quantitative model for allosteric control of mRR enzymatic activity based on molecular mass, ligand binding, and enzyme activity studies. In this model, nucleotide binding to the specificity site (s-site) drives formation of an active R1(2)R2(2) dimer, ATP or dATP binding to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
174
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(184 citation statements)
references
References 33 publications
9
174
1
Order By: Relevance
“…In many other organisms, specific regulatory mechanisms have also been described. These include the control of RNR activity via modulation of subunit degradation, modulation of the RNR quaternary structure, regulation of R1 activity by interaction with a small protein whose presence is modulated as a function of cell cycle, and control of specific subunit mRNA stability (6,(69)(70)(71). Integration, spatially and temporally, of these primary control mechanisms of RNR is, in general, not understood in any organism.…”
Section: Discussionmentioning
confidence: 99%
“…In many other organisms, specific regulatory mechanisms have also been described. These include the control of RNR activity via modulation of subunit degradation, modulation of the RNR quaternary structure, regulation of R1 activity by interaction with a small protein whose presence is modulated as a function of cell cycle, and control of specific subunit mRNA stability (6,(69)(70)(71). Integration, spatially and temporally, of these primary control mechanisms of RNR is, in general, not understood in any organism.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is important to note that several approaches that might answer this important question are available. For example, in mammalian cells, dUMP levels can be potentially downregulated by concentrating inhibition strategies on three critical enzyme activities that determine dUMP levels in cells: dUTPase (McIntosh and Haynes, 1997), RR (Kashlan et al, 2002), and dCydD (Bianchi et al, 1987). Unfortunately, genetic antisense RNA or other strategies that might be used to inhibit dUTPase would increase the size of dUTP pools that result in dUMP incorporation into DNA, and also would increase the probability that both FdUTP and dUTP would be incorporated into DNA (Caradonna and Cheng, 1980;.…”
Section: Unresolved Issues and Future Directionsmentioning
confidence: 99%
“…It may also be possible to interdict de novo synthesis of dUTP precursors by manipulating intracellular dNTP levels that regulate the ability of RR to produce deoxynucleotide precursors of dUMP. However, these strategies are complicated (Kashlan et al, 2002). Finally, dUMP and consequent dUTP levels can also be directly downregulated by inhibiting dCMPD and dCydD (Bianchi et al, 1987).…”
Section: Unresolved Issues and Future Directionsmentioning
confidence: 99%
“…Studying subunit interactions has been difficult by conventional methods because of ␣'s nucleotide-dependent aggregation state and the weak binding of ␣ and ␤, which is also nucleotide-dependent (21). Determination of apparent molecular masses of the active RNR complexes requires nucleotides in the analysis buffer, and thus protein detection by UV spectroscopy is obscured (18,23).A number of years ago, we reported on the inactivation of E. coli RNR by F 2 CDP (11, 12). We showed that 1 eq of F 2 CDP per E. coli RNR, presumably ␣ 2 ␤ 2 , in the presence of reductants, thioredoxin (TR) and TR reductase or DTT, is sufficient for enzyme inactivation and that the inactivation is accompanied by release of 2 fluoride ions and one cytosine (12).…”
mentioning
confidence: 99%